Living with coronary disease - Handler, Clive. (Springer London, 2007)
We are all more likely to die from a heart attack or a stroke than from any other condition. You should read this book if you are: A smoker Overweight Under stress The media are full of terms like angina, heart failure, coronary artery disease, thrombosis, but what do these mean to you? Gerry Coghlan and Clive Handler are experienced heart doctors who have written this book for people who have or might get coronary heart disease. This handy little book contains: Details on all the risk factors predisposing to heart disease Practical explanations of what is happening to your heart Explanations of all the tests a patient with heart disease may need Information on how to go about reducing your risk Advice to dispel people’s natural fear of the condition Guidance on how people can be more in control of their health Simple, direct language to simplify a highly technical and complex subject. Angina and heart attacks: overview -- The heart: how it works and what can go wrong -- Angina -- Heart attacks -- Cholesterol and other blood fats -- Food, drink, and weight -- Exercise and rehabilitation -- Diabetes -- High blood pressure (hypertension) -- Smoking -- Stress and coronary heart disease -- Heart problems in women -- Impotence and sexual aspects of coronary heart disease -- Tests and procedures for angina and heart attacks.